Superior Monitoring of Chemical Exposure Using Nanoconfinement Technology. (25th January 2021) - Apblett, Allen; Materer, Nicholas; Kadossov, Evgueni; Shaikh, Shoaib
ABSTRACT: Introduction: Military personnel are exposed to a broad range of potentially toxic compounds that can affect their health. These hazards are unpredictable because military service occurs in a wide array of uncontrolled environments. Therefore, a novel sorbent was developed that allows the fabrication of lightweight personal samplers that are both capable of sorbing an extremely wide range of organic chemical types and able to stabilize reactive compounds. Materials and Methods: OSU-6, a nanoporous silica, was provided by XploSafe LLC. The sorption capacity for several volatile organic compounds, the temperatures required for thermal desorption of adsorbed compounds, and the sampling rates for targeted analytes were determined. Results: The uptake capacity was found to be on average 1.5 g/g of sorbent. Analytes were not only held tightly but also could be desorbed upon heating the sorbate to temperatures below 150°C. Sampling rates for volatile organic compound by an OSU-6 sampler badge were on average, 5.7 times higher than those for a commercially available activated carbon badge. Theoretical calculations showed that sorption of volatile organic compounds on the surface of the tightly curved pore walls in OSU-6 is because of exceptionally strong cumulative addition of Van der Waals forces. Analytes could readily be analyzed by either solvent extraction or thermal desorption gas chromatography/mass spectrometry techniques. Excellent sampling rates, high concentrations of analytes in the OSU-6 sorbent matrix, and high desorption efficiencies (recoveries) were obtained using the thermal desorption method. Conclusions: The performance of the OSU-6 sorbent makes it highly capable of meeting the need for personal samplers that enable Individual Longitudinal Exposure Records development. It can adsorb an extremely wide array of different volatile organic compounds, it can stabilize reactive compounds, it has high sampling rates coupled with high capacity that provide both sensitivity and resistance to saturation, and it is unique in being very amenable to thermal desorption in combination with having strong sorbate binding and high capacity and surface area.